Quantum electrodynamics divergencies - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The problem of divergencies in Quantum Electrodynamics (QED) is discussed.Methods: The renormalisation group method is employed for dealing with infini- ties in QED.Results: The integrals in QED giving physical observables are finite.Conclusions: The divergencies in QED can be treated in a consistent way pro- viding mathematical rigorous results.
Keywords: Quantum Electrodynamics; Quantum Field Theory; Renormalisation Group